1977
DOI: 10.1007/bf00918673
|View full text |Cite
|
Sign up to set email alerts
|

Casein-mediated neutrophil chemotaxis

Abstract: This study was directed toward demonstrating an interaction between human polymorphonuclear leukocytes (PMNs) and the chemotactic factor,casein. Experiments conducted using fluorescein-labeled casein indicated that PMNs have a membrane receptor for this chemotactic factor. This receptor was specific for casein and was not found on lymphocytes. A direct parallel was shown between the binding of FITC--casein and the PMN chemotactic response to this protein. Binding to the receptor was optimal at 25 degrees C, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Patients with persistently raised blood eosinophil counts have a high incidence of endomyocardial fibrosis [Loffler's or eosinophilic endomyocardial disease (Chusid et al, 1975;Parrillo et al, 1979)] and it has been suggested that eosinophils themselves could cause the cardiac injury (Brockington et al, 1970). Initially experiments in vitro to see whether eosinophils could damage antibody-coated cells including heart cells showed little cytotoxicity (van Epps & Bankhurst, 1978) unless complement was also present (Parrillo & Fauci, 1978). However, the presence of degranulated eosinophils in the blood and cardiac tissues of patients with endomyocardial disease supported the suggestion that this disease was caused by eosinophil secretion products released from degranulated eosinophils (Spry & Tai, 1976).…”
mentioning
confidence: 99%
“…Patients with persistently raised blood eosinophil counts have a high incidence of endomyocardial fibrosis [Loffler's or eosinophilic endomyocardial disease (Chusid et al, 1975;Parrillo et al, 1979)] and it has been suggested that eosinophils themselves could cause the cardiac injury (Brockington et al, 1970). Initially experiments in vitro to see whether eosinophils could damage antibody-coated cells including heart cells showed little cytotoxicity (van Epps & Bankhurst, 1978) unless complement was also present (Parrillo & Fauci, 1978). However, the presence of degranulated eosinophils in the blood and cardiac tissues of patients with endomyocardial disease supported the suggestion that this disease was caused by eosinophil secretion products released from degranulated eosinophils (Spry & Tai, 1976).…”
mentioning
confidence: 99%
“…As PMNs are critical players in inflammatory and tumorigenic processes in the colon [5,9,38,39], we investigated the significance of increased LDs and loss of FOXO3 in PMNs' activity. Intraperitoneal PMNs were obtained from wild type (WT) and FOXO3 knock-out (KO) mice following casein injection [40,41]. After PMNs enrichment, the final fraction contained more than 90% PMNs (FACS assessment of surface marker Ly6G), and peritoneal PMNs in FOXO3 KO mice were increased compared to WT.…”
Section: Increased Migratory Activity Of Pmns Is Associated With Elev...mentioning
confidence: 99%
“…In vitro experiments reported caseininduced macrophage and neutrophil migration. [4][5][6] Most proteins are digested into peptides and amino acids when a food protein is taken orally. Previously, it has been reported that YPVEP, produced by digesting β-casein with actinase, derived from actinomycetes, helps migrate mouse macrophages.…”
Section: Introductionmentioning
confidence: 99%